2003
DOI: 10.1103/physrevlett.91.090402
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Spin Exchange Interactions of Ultracold Atoms in Optical Lattices

Abstract: We describe a general technique that allows one to induce and control strong interaction between spin states of neighboring atoms in an optical lattice. We show that the properties of spin exchange interactions, such as magnitude, sign, and anisotropy, can be designed by adjusting the optical potentials. We illustrate how this technique can be used to efficiently ''engineer'' quantum spin systems with desired properties, for specific examples ranging from scalable quantum computation to probing a model with co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1,334
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,174 publications
(1,339 citation statements)
references
References 19 publications
3
1,334
1
1
Order By: Relevance
“…Since it utilizes the superposition of quantum phases in its hardware, a quantum simulator does not suffer from the notorious sign problem. From a condensed matter perspective, this is extremely interesting because highly non-trivial many-body systems, such as geometrically frustrated quantum antiferromagnets [30], various spin liquids, or high-temperature superconductors [31] can perhaps be quantum simulated, despite the fact that the sign problem prevents numerical simulations on classical computers. It was a significant breakthrough, when a non-trivial quantum phase transition separating a Mott insulator (with localized particles) from a superfluid, was first quantum simulated by implementing the BoseHubbard model with cold atoms in an optical lattice [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since it utilizes the superposition of quantum phases in its hardware, a quantum simulator does not suffer from the notorious sign problem. From a condensed matter perspective, this is extremely interesting because highly non-trivial many-body systems, such as geometrically frustrated quantum antiferromagnets [30], various spin liquids, or high-temperature superconductors [31] can perhaps be quantum simulated, despite the fact that the sign problem prevents numerical simulations on classical computers. It was a significant breakthrough, when a non-trivial quantum phase transition separating a Mott insulator (with localized particles) from a superfluid, was first quantum simulated by implementing the BoseHubbard model with cold atoms in an optical lattice [32].…”
Section: Introductionmentioning
confidence: 99%
“…A possible way to realize Kitaev model on optical lattice has been proposed [3]. Recently, studies for the Kitaev-Heisenberg (KH) model showed that this peculiar quantum SL is possible to be realized in iridates A 2 IrO 3 (A=Na, Li) because of a strong intrinsic spin-orbital (SO) coupling of the 5d electron of iridium ions [4,5] .…”
mentioning
confidence: 99%
“…In this respect it is important to emphasize again that our approach represents the fermonic degrees of freedom within individual vortex sectors. This is fundamentally different from approaches to Kitaev model construction using ultracold atoms [69][70][71] or superconducting electronics [72]. In these realizations, one seeks to engineer the actual spin-spin interactions of the Kitaev systems explicitly.…”
Section: Discussionmentioning
confidence: 99%